The influence of the transducer bandwidth on the efficient Golay codes compression - Trots, Ihor; Nowicki, Andrzej; Secomski, Wojciech; Tymkiewicz, Ryszard (Archives of Acoustics, 2007)
The maximization of penetration depth with concurrent retaining or enhancement of imageresolution constitutes one of the time invariant challenges in ultrasound imaging. To solve thisproblem a pulse compression technique employing long coded sequences is now under intensiveinvestigation and in fact some of the corresponding techniques were already implementedin commercial scanning machines.This paper investigates the influence of the effective bandwidth of the transducer on thebehaviour of the encoding/compression technique and its potential influence on the axial resolution.We have investigated two different bits lengths – one and two periods – in the Golaysequences resulting in substantial difference of the bandwidth of the transmitted sequences.Three transducers with different fractional bandwidths were used in the experiments: 6 MHzfocused transducer with 25% fractional bandwidth, 4.4 MHz flat transducer with 58% fractionalbandwidth and 6 MHz flat, composite transducer with 80% fractional bandwidth. Theexperimental results are clearly showing that the elongation of the Golay single bit length (twocycles in our case) compensates for the limited transducer bandwidth. For 25% bandwidthpeak-to-peak echo increased by 1.89 times; for 58% bandwidth peak-to-peak echo amplitudeincreased by 1.62 times, and for 80% bandwidth peak-to-peak echo increased by 1.47 times.